A flexible current tracking control of sensorless induction motors via adaptive observer. (October 2019) - Li, Li; Zhang, Zhongcai; Wang, Chunxiao
Abstract: In this article, an interconnected adaptive observer-based backstepping control method is proposed to achieve sensorless current control without persistent excitation condition. Based on the stability theories of mathematics, an effective observer utilized to estimate the fluxes and external load is given. It has a good foundation for breaking the limitation caused by the coupling between the control process and the parameter estimation course. The characteristic of the uncoupling can make the control range for currents more wider. Due to the effective online tracking and the good adaptability of the designed observers, the control effect shows good robustness to the parameters. Finally, numerical simulations are provided to intuitively illustrate the effectiveness and the superiority of the theoretical results. Highlights: An interconnected adaptive observer-based Backstepping control method is proposed to achieve sensorless current control for sensorless induction motors without persistent excitation condition. The idea of estimating the external load in the above observer can provide a new idea for designing a disturbance observer for the system with disturbances and incompletely measurable states. The introducing of the interconnected adaptive observer-based Backstepping control method broken the intersections between the estimation of system variables and the design of controllers.